(untitled) (GYMNASIUM, 2008)
An outstanding form of mountain tourism, the rock climbing has always been both a challenge and an attraction especially for adolescents and young people. Such an approach meets the needs for self-assertion, recognition, confirmation, self-evaluation and that of going beyond internal and external limitations. This paper aims at two targets. The first one is to point to certain aspects that could lead to increasing the efficiency of teaching mountain climbing lessons. The second one is to emphasize the ways to trigger a faster learning process.